THE IMPACT OF THE GREATER ARAB FREE TRADE AREA ON ALGERIA’S INTRA-ARAB FOREIGN TRADE (International Journal of Innovative Technologies in Economy, 2025)
This study aims to examine the reality of Algeria’s foreign trade in recent years within the framework of trade liberalization and the country's efforts to diversify its exports, reduce its import bill, and stimulate other productive sectors. It also seeks to assess the extent to which Algeria’s foreign trade has been affected by its accession to the Greater Arab Free Trade Area (GAFTA).The study concluded that Algeria’s intra-Arab trade with other Arab countries remains limited and has not achieved the objectives set for joining this area, as it did not exceed 5 billion USD. Tunisia is considered Algeria’s largest Arab economic partner, followed by Saudi Arabia, Egypt, and the United Arab Emirates.